Numerical modeling of the abdominal wall biomechanics and experimental analysis for model validation - Spadoni, Silvia; Todros, Silvia; Pavan, Piero G. (Frontiers in Bioengineering and Biotechnology, 2024)
The evaluation of the biomechanics of the abdominal wall is particularly important to understand the onset of pathological conditions related to weakening and injury of the abdominal muscles. A better understanding of the biomechanics of the abdominal wall could be a breakthrough in the development of new therapeutic approaches. For this purpose, several studies in the literature propose finite element models of the human abdomen, based on the geometry of the abdominal wall from medical images and on constitutive formulations describing the mechanical behavior of fascial and muscular tissues. The biomechanics of the abdominal wall depends on the passive mechanical properties of fascial and muscle tissue, on the activation of abdominal muscles, and on the variable intra-abdominal pressure. To assess the quantitative contribution of these features to the development and validation of reliable numerical models, experimental data are fundamental. This work presents a review of the state of the art of numerical models developed to investigate abdominal wall biomechanics. Different experimental techniques, which can provide data for model validation, are also presented. These include electromyography, ultrasound imaging, intraabdominal pressure measurements, abdominal surface deformation, and stiffness/compliance measurements.